PENGARUH PENERAPAN MODEL INQUIRY BASED LEARNING DENGAN BERBANTUAN MEDIA ULAR TANGGA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII DI SMPN 1 MATARAM - Julkifli; Edy Herianto; Edy Kurniawansyah (Jurnal Pendidikan Sosial Keberagaman, 2026)
Based on the researcher's preliminary observations conducted at SMP Negeri 1 Mataram, several issues were identified in the Pancasila and Citizenship Education (PPKn) learning process. Specifically, in classes VIII-A and VIII-D, a number of students remained inactive during lessons. This lack of engagement was evident when students failed to respond to the teacher's stimuli, such as questions, prompts to express ideas, or other instructions. Furthermore, interviews with several students revealed that their boredom and drowsiness during class were caused by the teacher's uninnovative learning models. The teacher primarily relied on writing on the board and used only a single learning model, which failed to stimulate higher-order thinking among students. In response to these issues, the researcher collaborated with the PPKn teacher for classes VIII-A and VIII-D to select and implement an appropriate learning model capable of fostering motivation, enhancing critical thinking, and improving the overall success of the PPKn learning process. This study aims to improve students' critical thinking skills through the implementation of the inquiry-based learning model assisted by snakes and ladders media. Data collection techniques included observations and tests. The results of the study demonstrate the significant impact of implementing the inquiry-based learning model assisted by snakes and ladders media among grade VIII-A students at SMPN 1 Mataram. The statistical analysis showed a significance level of (0.002) < 0.05, meaning that there is a significant difference before and after the implementation of the model. Consequently, the inquiry-based learning model assisted by snakes and ladders media can serve as an effective alternative for innovative learning to enhance both the quality of education and junior high school students' critical thinking. Keywords: Inquiry-based learning model, snakes and ladders media, Critical Thinking, PPKn.